Do Islamic social entrepreneurship moderate Islamic leadership and emotional intelligence? Evidence from micro and small enterprises fostered by ‘Aisyiyah - Nurul Asfiah (Journal of Innovation in Business and Economics, 2021)
This study aims to understand Islamic social entrepreneurship in moderating the influence of Islamic leadership and emotional intelligence to improve Micro and Small Enterprises (SMEs). Another objective of this study is to determine the effect of Islamic leadership, emotional intelligence, and Islamic social entrepreneurship on business performance. This research is quantitative research, whose population is a group of SMEs fostered by 'Aisyiyah East Java so that 150 respondents were determined. This amount is calculated by non-probability sampling and judgmental sampling techniques based on the researcher's considerations. The sample was decided to be used due to existing uncertain population, and the collection of questionnaires using Google forms. All variables are valid and reliable; data analysis using path analysis technique with Smart PLS 3.0 software found a direct and indirect effect of Islamic social entrepreneurship variable on SME business performance. This analysis also shows that Islamic leadership and emotional intelligence have a significant impact on business performance.